2020
DOI: 10.1016/j.jpeds.2020.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Outcomes of Hospitalized and Critically Ill Children and Adolescents with Coronavirus Disease 2019 at a Tertiary Care Medical Center in New York City

Abstract: Objective To describe the clinical profiles and risk factors for critical illness in hospitalized children and adolescents with coronavirus disease 2019 (COVID-19). Study design Children 1 month to 21 years of age with COVID-19 from a single tertiary care children's hospital between March 15 and April 13, 2020 were included. Demographic and clinical data were collected. Results In total, 67 children tested positive for COVID-19; 21 (31.3%) were managed as outpatients. Of 46 admitted patients, 33 (72%) were adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
352
7
30

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(424 citation statements)
references
References 22 publications
35
352
7
30
Order By: Relevance
“…and data regarding the secondary outcomes was reported in 43 studies(8, 9, 16-25, 31, 32, 34-38, 42, 43, 45-55, 57-61, 64, 67, 68, 70-72). A study by Chao et al(73) was exclusively performed on children and thus was not included in the meta-analysis. Included publications were all observational in nature, published in 2020.…”
mentioning
confidence: 99%
“…and data regarding the secondary outcomes was reported in 43 studies(8, 9, 16-25, 31, 32, 34-38, 42, 43, 45-55, 57-61, 64, 67, 68, 70-72). A study by Chao et al(73) was exclusively performed on children and thus was not included in the meta-analysis. Included publications were all observational in nature, published in 2020.…”
mentioning
confidence: 99%
“…[12][13][14]18 Hb levels were normal in asymptomatic children with COVID-19 but also in severe disease, 12,18 and did not differ between children admitted to the ICU or to a medical unit. [12][13][14] Anemia was a common feature in the children with a Kawasaki-like disease associated with SARS-CoV-2 infection, called multisystem inflammatory syndrome. 39 One case report described a 17-year-old male with a history of refractory chronic immune thrombocytopenia that manifested as autoimmune hemolytic anemia during infection with SARS-CoV-2.…”
Section: Abnormalities In the Red Blood Cell Count In Children With Cmentioning
confidence: 85%
“…Original studies published up to July 27, 2020 [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] providing data on white blood cell (WBC) abnormalities in children with COVID-19 are shown in Table 1.…”
Section: Abnormalities In the White Blood Cell Count In Children Withmentioning
confidence: 99%
“…2,3 ARDS has been reported in 3% to 17% of all COVID-19 patients and in about 60% of children requiring intensive care. 4 Our patient met the Berlin criteria for severe ARDS with PaO 2 /FiO 2 ratio less than 100. Our patient had worsening hypoxemia and increased inflammatory markers of CRP and procalcitonin, low platelets, and initial acute kidney injury similar to that seen by Chao et al 4 The severe transaminitis noted in our patient has not been reported in the pediatric studies published thus far.…”
Section: Ards In An Ex-premature Infant With Bronchopulmonary Dysplasmentioning
confidence: 66%